2020
DOI: 10.1111/lam.13283
|View full text |Cite
|
Sign up to set email alerts
|

Virulence properties and antimicrobial resistance of Pseudomonas aeruginosa isolated from cave waters at Roraima Tepui, Guayana Highlands

Abstract: Pseudomonas aeruginosa is a prominent member of emerging waterborne pathogens. The environmental reservoirs of multi‐resistant phenotypes and other virulence factors in this bacterium are poorly understood. Our study aimed to determine the virulence properties of P. aeruginosa isolated from Roraima Sur Cave (RSC) waters at Guayana Highlands. Based on the best identification at species level by biochemical tests, 16S rRNA sequencing and phylogenetic inferences, one RSC isolate named LG11 was characterized for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…Comparative analyses of enzyme production in environmental isolates of P. aeruginosa have also shed light on the enzymatic profiles of these strains [ 24 , 25 ]. The absence of pyocyanin production in any environmental isolates is consistent with previous studies that reported low frequencies or the absence of pyocyanin in environmental strains of P. aeruginosa [ 26 , 27 ]. Moreover, the overall patterns of enzyme production in environmental isolates differ from those observed in clinical isolates, indicating that P. aeruginosa strains adapt their enzymatic pathways based on the site of infection or environmental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Comparative analyses of enzyme production in environmental isolates of P. aeruginosa have also shed light on the enzymatic profiles of these strains [ 24 , 25 ]. The absence of pyocyanin production in any environmental isolates is consistent with previous studies that reported low frequencies or the absence of pyocyanin in environmental strains of P. aeruginosa [ 26 , 27 ]. Moreover, the overall patterns of enzyme production in environmental isolates differ from those observed in clinical isolates, indicating that P. aeruginosa strains adapt their enzymatic pathways based on the site of infection or environmental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of resistance genes was determined with a percentage identity (ID) threshold of 90% over the length of the reference sequence whereas β-lactamase variants were determined with a percentage ID threshold of 100%. In addition, potential virulence factor-related genes, from which a selection was made based on previous studies [9][10][11], were identified by the virulence factor database (VFDB, http://www. mgc.ac.cn/VFs/) [12].…”
Section: Whole Genome Sequencingmentioning
confidence: 99%
“…Silicate caves have been discovered in 1972 in the table mountains, or tepuis, in Guiana Highlands in South America, especially in southeastern Venezuela and western Guiana [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Tepuis are table mountains or mesetas composed of Paleoproterozoic quartzites and sandstones, surrounded by steep cliffs [ 18 ]. In the process of exploring these isolated environments, karst structures with numerous cave systems and unique silica deposits have been found [ 15 , 19 ].…”
Section: Introductionmentioning
confidence: 99%